Salt Intake: ¿Risk or Need? - Emiliano Nicolás Diez y Martínez de la Cotera; Mikhail Benet Rodríguez; Alain Francisco Morejón Giraldoni; Rubén García Núñez (Revista Finlay)
A literary review on salt intake and its uses throughout the different stages in the history of mankind was conducted. It addresses issues related to salt concentrations in the human body, its physiological functions that are essential for homeostatic control, as well as the complications when salt levels are below or over the physiological limits. Different studies were analyzed including the contradictions they all present on the damage that salt intake can cause to human health. Population groups are defined as salt sensitive (SS) and salt resistant (SR) according to study that was conducted as well as to the possible causes for their variations. Conclusions are drawn on the risks and benefits of salt intake. Intervention is recommended for balanced consumption, both for individuals and for populations.